Effect of lymph node dissection on the outcomes of upper tract urothelial carcinomas: a meta-analysis. Issue 6 (June 2014) - Yang, Deyong; Chen, Qiwei; Song, Xishuang; Wang, Jianbo; Che, Xiangyu; Zhu, Zheng; Zheng, Wei; Wang, Lina
<x xml:space="preserve">Abstract</x> A systematic search was conducted in PubMed, Cochrane Library. 6032 patients were included. There was no significant difference in survival between LND and NLND (non-lymph node dissection) among the patients. However, the patients in the LND group had more advanced tumour stages and grades (p < 0.001). In addition, among the muscle-invasive patients, LND demonstrated remarkable CSS improvement compared with NLND (HR: 2.19; 95% CI: 1.26–3.80; p = 0.005). Moreover, subgroup analyses found that patients with muscle-invasive UTUC had better CSS (HR: 1.22; 95% CI: 1.02–1.45; p < 0.001) than those patients with pN0 compared to pNx (NLND). In terms of RFS, the results showed no difference in the survival rates between pN0 and pNx patients in the subgroup of patients with muscle-invasive UTUC (HR: 1.40; 95% CI: 0.84–2.23; p = 0.19). Our meta-analysis supports that LND may prolong the CSS and RFS of UTUC, especially for patients with muscle-invasive UTUC.